Early Postoperative Prediction of Clinically Relevant Pancreatic Fistula after Pancreaticoduodenectomy: usefulness of C-reactive Protein. Issue 7 (July 2017) - Partelli, Stefano; Pecorelli, Nicolò; Muffatti, Francesca; Belfiori, Giulio; Crippa, Stefano; Piazzai, Francesco; Castoldi, Renato; Marmorale, Cristina; Balzano, Gianpaolo; Falconi, Massimo
Abstract: Background: An early recognition of clinically relevant pancreatic fistula (PF) after pancreaticoduodenectomy (PD) is essential. Methods: All consecutive patients who underwent PD in two institutions were included (2013–2015). In all patients amylase value in drains (AVD) was evaluated in postoperative day 1 (POD1). White-blood cell count (WBC), serum pancreatic amylase (SPA) and C-reactive protein (CRP) were routinely evaluated in POD1, POD2, and POD3. Receiver operator characteristic (ROC) curves were performed. Significant diagnostic cut-offs were tested in a multivariate model. Results: Overall, 463 patients underwent PD. Postoperative morbidity and mortality were 58% and 4%, respectively. Sixty-four patients (14%) had a clinically relevant PF (grade B or C). ROC curve analyses revealed that AVD on POD1 had the greatest area under the curve value (0.881, P  < 0.0001) followed by CRP on POD3 (0.796, P  < 0.0001). Multivariable analysis identified male gender (OR 2.29 95%CI: 1.12–4.70, P  = 0.023), AVD on POD1>500 U/l (OR 21.72, 95%CI: 7.41–63.67, P  < 0.0001), CRP on POD2 > 150 mg/l (OR 3.480, 95%CI: 1.21–9.99, P  = 0.021), and CRP on POD3 > 185 mg/l (OR 6.738, 95%CI: 1.91–23.78, P  = 0.003) as independent predictors of clinically relevant PF. Conclusion: The combination of CRP and AVD was effective in the early prediction of clinically relevant POPF after PD.